The Role of the Family Hope Program (PKH) in Improving the Social Welfare of the Muslim Community in Pematangsiantar City - Simamora, Purnamasari; Tanjung, Muaz (Electronic Journal of Education, Social Economics and Technology, 2025)
The Family Hope Program (PKH) is an initiative of the Indonesian government that aims to reduce poverty and improve the quality of human resources, especially among the poor. PKH provides cash assistance to Beneficiary Families (KPM) who meet certain criteria, focusing on improving access to education and health services. This study aims to analyze the contribution of PKH in improving the social welfare of the Muslim community in Martoba Village, North Siantar District, as well as identify supporting and inhibiting factors for implementing the program. The research method used is qualitative, with data collection techniques through interviews, observations, and documentation. The study results show that PKH has significantly improved access to health, education, and social welfare for KPM. However, there are challenges in validating beneficiary data and public awareness of program obligations. Recommendations for improvement include increasing training for PKH facilitators, program socialization, and periodic evaluations to adjust to community needs. With these steps, it is hoped that PKH can be more effective in breaking the cycle of poverty and improving social welfare in the area.